1
$\begingroup$

I need a little bit of assistance with the following problem:

Calculate general Taylor Series and the first 3 terms of the Taylor series centered at 2 of the function

f(x) = ln(x^2 + 2x + 1)

I know the first step would be calculating multiple derivatives as below:

f'(x)=2/(x+1)

f"(x)= -2/(x+1)^2

f"'(x)=4/(x+1)^3

f""(x)= -12/(x+1)^4

f""'(x)=48/(x+1)^5

What would be the next step after doing this? I guess my issue is turning this into a taylor series using the formula.

$\endgroup$
0

1 Answer 1

2
$\begingroup$

Hint: Since $f(x)=\log\bigl((x+1)^2\bigr)=2\log(x+1)$, then$$f'(x)=\frac2{x+1}=\frac2{3+(x-2)}=\frac23\cdot\frac1{1+\frac{x-2}3}.$$

$\endgroup$
10
  • $\begingroup$ where did you get the 3 from? and how would you turn this into a taylor series? $\endgroup$ Apr 28, 2019 at 14:46
  • $\begingroup$ The $3$ comes from the difference between $x+1$ and $x-2$. And$$\frac1{1+\frac{x-2}3}=1-\frac{x-2}3+\frac{(x-2)^2}{3^2}-\frac{(x-2)^3}{3^3}+\cdots$$ $\endgroup$ Apr 28, 2019 at 14:48
  • $\begingroup$ and how does this turn into a taylor series? $\endgroup$ Apr 28, 2019 at 14:57
  • $\begingroup$ Since $f'(x)$ is the sum of that power series and since $f(2)=\log9$, then$$f(x)=\log9+2(x-2)-\frac{2(x-2)^2}{2\times3}+\frac{2(x-2)^3}{3\times3^2}-\frac{2(x-2)^4}{4\times3^3}+\cdots$$ $\endgroup$ Apr 28, 2019 at 14:59
  • 1
    $\begingroup$ The summation index doesn't matter. The $(x-2)^n$ terms are given instead by $(x-2)^k$ terms in the expansion I gave. $\endgroup$ Apr 28, 2019 at 15:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.